Pengaruh penggunaan tepung ulat kandang (Alphitobius diaperinus) dalam pakan terhadap penampilan produksi ayam pedaging - Hudan Allama; Osfar Sjofjan; Eko Widodo; Heni Setyo Prayogi (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2012)
Abstract: The objective of this research was to evaluate the effect of lesser mealworm meal in feed on the performance of broiler. The materials used for this experiment were 100 Lohmann strain broiler chicks with average body weigth 257.55 + 26.36 g. The treatments were P0 = basal feed, P1 = 0,5% lesser mealworm meal, P2 = 1% lesser mealworm meal, and P3 = 1,5 % lesser mealworm meal and P4 = 2% lesser mealworm meal. The measured variables were feed consumption, body weight gain, feed conversion, mortality and Income Over Feed Cost (IOFC). Data obtained in this study were analysed by ANOVA Completely Randomized Design consisting of 5 treatments and 4 replications. Duncan’s Multiple Range Test were used to analize the difference between the treatments.The results of this research showed that the use of lesser mealworm meal as feed ingredient did not significantly influenced (P > 0.05) feed consumption, weight gain, feed conversion, mortality and very significantly influenced (P > 0.01) Income Over Feed Cost (IOFC). It can be concluded that the use of lesser mealworm meal until level of 2 % as feed addition doesn’t improve broiler production performances.Keywords : Lesser mealworm, and broiler